2012
DOI: 10.1007/s10290-012-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

Firms’ exporting and importing activities: is there a two-way relationship?

Abstract: The literature on firm heterogeneity and trade has highlighted that most\ud trading firms tend to engage in both importing and exporting activities. This paper provides some evidence that helps understanding to what extent this is the result of a two-way relationship. Using firm-level data for a group of 27 Eastern European and\ud Central Asian countries from the World Bank Business Environment and Enterprise Performance Survey (BEEPS) over the period 2002–2008, we estimate a bivariate probit model of exportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 63 publications
2
78
3
1
Order By: Relevance
“…Indeed, during the crisis the probability of entry in foreign markets did not significantly change with respect to the previous period and, when total exports are considered, the firm probability to stop exporting in fact decreased. In addition, in line with the existing evidence on the positive association between firm importing and exporting (Kasahara and Lapham, 2008;Muû ls and Pisu, 2009;Aristei et al, 2013;Lo Turco and Maggioni, 2013) which may prove more important under the economic downturn (Behrens et al, 2012), from panel B it emerges that importers were actually more likely to start exporting in the recession. The likeliness of the drop of a product from the firm export basket was however increased by the crisis, thus contributing to explain the export slump, even if this result is not confirmed for regular exports.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Indeed, during the crisis the probability of entry in foreign markets did not significantly change with respect to the previous period and, when total exports are considered, the firm probability to stop exporting in fact decreased. In addition, in line with the existing evidence on the positive association between firm importing and exporting (Kasahara and Lapham, 2008;Muû ls and Pisu, 2009;Aristei et al, 2013;Lo Turco and Maggioni, 2013) which may prove more important under the economic downturn (Behrens et al, 2012), from panel B it emerges that importers were actually more likely to start exporting in the recession. The likeliness of the drop of a product from the firm export basket was however increased by the crisis, thus contributing to explain the export slump, even if this result is not confirmed for regular exports.…”
Section: Resultssupporting
confidence: 74%
“…As far as firm access to import markets is concerned we show that importing, as expected, favours export activity in the crisis. Imported inputs may foster export activity thanks to the existence of common sunk costs and/or the enhancement of competitiveness occurring through cost saving or technology transfer (Kasahara and Lapham, 2008;Muû ls and Pisu, 2009;Aristei et al, 2013;Lo Turco and Maggioni, 2013). We show that this linkage is strengthened during the crisis.…”
Section: Summary Of the Findings And Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Also they find that sunk costs decrease when the complementary activity was carried out the past year, meaning that common fixed costs exist, and obtain a higher sunk cost for imports than for exports. Secondly, Aristei et al (2013) using data for Eastern European and Central Asian firms obtain a high degree of hysteresis for both activities, but higher for exports than for imports and find that past imports affect the probability to export in the current year but not the other way around.The numbers of studies focused on MENA countries are few. Related to the role that imported intermediates could play in technological diffusion, Brach (2010) assesses the role of technological readiness in the MENA region and the implications for Egypt.…”
mentioning
confidence: 94%
“…This is studied by Aristei et al (2013) who used firm-level survey data from 27 countries and found that a firm's importing increases its exports while a firm's exporting does not have any effect on its imports. Turco and Maggioni (2013) did a similar analysis for Italian firms and found that importers are more likely to start exporting.…”
Section: Introductionmentioning
confidence: 99%